Nutritional protocols that shift ruminal microbiota to improve the feedlot performance of Nellore cattle differing in marbling EPD - Silvestre, Antonio M. [UNESP]; Squizatti, Mariana M. [UNESP]; Felizari, Luana D. [UNESP]; Demartini, Breno L. [UNESP]; Silva, Leandro A. F. [UNESP]; Casali, Daniel M. [UNESP]; Souza, Johnny M. [UNESP]; Virgínio, Gercino F. [UNESP]; Suen, Garret; Millen, Danilo D. [UNESP] (Springer Nature, 2025)
This study evaluated the effects of high-moisture corn (HMC), rumen-protected fat (CSFA), and organic zinc plus chromium (ZnCr) supplementation, alone or in combination, on feedlot performance, rumen microbiota, carcass traits, and feeding behavior of Nellore cattle with divergent marbling EPD. A total of 150 Nellore yearling bulls were classified into high and low EPD groups and assigned to five diets: (1) fine ground corn (FGC); (2) high-moisture corn (HMC); (3) FGC + calcium salts of fatty acids (FGC + CSFA); (4) HMC + CSFA; and (5) HMC + CSFA + ZnCr (organic zinc and chromium added). The HMC improved average daily gain and gain-to-feed ratio while reducing dry matter intake. The CSFA inclusion enhanced carcass traits and reduced incidence of rumenitis, improving rumen health. The ZnCr supplementation increased glucose availability and dressing percentage, especially in high-EPD animals. Genetic predisposition for marbling influenced dietary responses, with high-EPD bulls showing greater fat deposition and energy efficiency. Rumen microbiota composition was altered by corn processing, CSFA, and ZnCr, particularly affecting specific taxa such as Prevotella, Butyrivibrio, and Firmicutes. Feeding behavior and ruminal morphometry also varied with diet and genetic group. In conclusion, it is recommended to combine HMC and CSFA, while ZnCr proves to be most effective in marbling-genetically predisposed cattle.